Expansion of rDNA and pericentromere satellite repeats in the genomes of bank voles Myodes glareolus exposed to environmental radionuclides. Issue 13 (25th May 2021) - Jernfors, Toni; Danforth, John; Kesäniemi, Jenni; Lavrinienko, Anton; Tukalenko, Eugene; Fajkus, Jiří; Dvořáčková, Martina; Mappes, Tapio; Watts, Phillip C.
Abstract: Altered copy number of certain highly repetitive regions of the genome, such as satellite DNA within heterochromatin and ribosomal RNA loci (rDNA), is hypothesized to help safeguard the genome against damage derived from external stressors. We quantified copy number of the 18S rDNA and a pericentromeric satellite DNA (Msat‐160) in bank voles ( Myodes glareolus ) inhabiting the Chernobyl Exclusion Zone (CEZ), an area that is contaminated by radionuclides and where organisms are exposed to elevated levels of ionizing radiation. We found a significant increase in 18S rDNA and Msat‐160 content in the genomes of bank voles from contaminated locations within the CEZ compared with animals from uncontaminated locations. Moreover, 18S rDNA and Msat‐160 copy number were positively correlated in the genomes of bank voles from uncontaminated, but not in the genomes of animals inhabiting contaminated, areas. These results show the capacity for local‐scale geographic variation in genome architecture and are consistent with the genomic safeguard hypothesis. Disruption of cellular processes related to genomic stability appears to be a hallmark effect in bank voles inhabiting areas contaminated by radionuclides. Abstract : Bank voles captured from locations contaminated with radionuclides in the Chernobyl Exclusion Zone exhibit increased copy numbers of ribosomal DNA and pericentromeric satellite Msat‐160, as well as a breakdown of genomic correlation between these loci compared with control. Copy‐number variation in heterochromatic repetitive loci may have adaptive significance. ​